Assessment of the application for renewal of authorisation of l‐histidine monohydrochloride monohydrate produced with Escherichia coli NITE SD 00268 for salmonids and its extension of use to other fin fish. (30th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐histidine monohydrochloride (HCl) monohydrate produced by fermentation using Escherichia coli NITE SD 00268 in the context of the renewal of the authorisation for salmonids when used as a nutritional additive. In addition, the applicant requested the extension of use of the additive for other fin fish. The applicant has provided evidence that the composition of the additive currently in the market complies with the conditions of authorisation. The production strain has been modified by conventional mutagenesis and it does not raise safety concerns. The use of l ‐histidine HCl monohydrate produced by fermentation using E. coli NITE SD 00268 is safe for salmonids and other fin fish when used as a nutritional additive to supplement the diet in appropriate amounts to cover the nutritional requirements, depending on the species, the physiological state of the animal, the performance level, the environmental conditions, the background amino acid composition of the unsupplemented diet and the status of some essential trace elements such as copper and zinc. The FEEDAP Panel considers the maximum total concentration of 1.7% histidine in feed for salmonids proposed by the applicant as safe. For other fin fish species, the level of 1.7% appears to cause adverse effects. Therefore, it is not possible to define a maximum concentration of histidine in fish other than salmonids as it depends on histidine nutritional requirements in the different fish species. The use of the authorised additive in salmonids production does not pose a risk for consumers, and the proposed maximum total concentration of 1.7% histidine in feed is considered safe for the consumer. l ‐Histidine HCl monohydrate produced using E. coli NITE SD 00268 supplemented at levels appropriate to cover the nutritional requirements of fish other than salmonids is considered safe for the consumer. The additive under assessment is not a skin irritant. In the absence of data, it is not possible to conclude on the potential of the additive to be toxic by inhalation, irritant to eyes or a skin sensitiser. The amino acid l ‐histidine is a natural component of plants and animals. The use of the additive under assessment in animal nutrition does not represent a risk to the environment. The additive is considered an efficacious source of the amino acid l ‐histidine for fish species.